KEDUDUKAN HAKIM WANITA DALAM PERSPEKTIF FUQAHĂ’ (Studi Komparatif Imām Abū Hanīfah dan Ibn Jarīr At-Thabarī) - Siti Mualifah; Adang Djumhur Salikin; Ubaidillah Ubaidillah (IAIN Syekh Nurjati Cirebon, 2020)
Judges are a very urgent profession, because judges are one of the highest positions in Islam. This position is higher when compared to the mufti, because the task of the judge is not just to declare the law, but also to impose a sentence in which the results of the decision must be implemented and obeyed. So that the requirements and due diligence must be upheld in a democratic, fair and honest manner. In the discourse on the terms and legal status of women serving as judges, there was a difference of opinion among the jurists and caused controversy among the Imams of the schools. This study aims to answer the questions that formulate the problem: